Australian parent and sibling perspectives on the impact of paediatric acquired brain injury on family relationships during the first 6 weeks at home. (26th July 2022) - Hickey, Lyndal; Anderson, Vicki; Jordan, Brigid
Abstract: This study explores the impact of paediatric acquired brain injury (ABI) on family relationships. Twenty‐three families ( n  = 18 mothers, n  = 7 fathers, and n  = 4 siblings) of children who sustained an ABI requiring treatment from inpatient acute and rehabilitation services reported on their perceptions regarding changes in family relationships since the injured child's return home. Thematic analysis of survey data was conducted. Family members (parents and siblings) described four themes: (1) negative changes in sibling interactions; (2) role changes arising from an increase in parental expectations of non‐injured siblings; (3) family system challenges in balancing needs within the parent–child dyad and sibling subsystems; and (4) supporting emotional responses within the family system. Findings reveal a critical time for families as they resume full care of the injured child at home. Clinical implications for social workers and other rehabilitation clinicians are explored.